2013
DOI: 10.1523/jneurosci.4999-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase 1 Receptor Internalization and Endosomal Signaling Mediate the Pituitary Adenylate Cyclase Activating Polypeptide-Induced Increase in Guinea Pig Cardiac Neuron Excitability

Abstract: Following G protein-coupled receptor activation and signaling at the plasma membrane, the receptor complex often is rapidly internalized via endocytic vesicles for trafficking into various intracellular compartments and pathways. Formation of signaling endosomes is recognized to be a mechanism to produce sustained intracellular signals, which may be distinct from those generated at the cell surface, for cellular responses including growth, differentiation and survival. Pituitary adenylate cyclase activating po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 42 publications
(77 reference statements)
14
100
1
Order By: Relevance
“…Our previous studies demonstrated that treatment with the inhibitors Pitstop 2 and dynasore or temperature reduction to blunt clathrin-and dynamin-dependent endocytosis did not suppress PACAP-induced cAMP generation in sympathetic neuronal cultures, suggesting that the second messenger was generated primarily at the plasma membrane of primary neurons (31). Thus we evaluated whether the same mechanisms could be observed in the PAC1 receptor-expressing cell lines.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Our previous studies demonstrated that treatment with the inhibitors Pitstop 2 and dynasore or temperature reduction to blunt clathrin-and dynamin-dependent endocytosis did not suppress PACAP-induced cAMP generation in sympathetic neuronal cultures, suggesting that the second messenger was generated primarily at the plasma membrane of primary neurons (31). Thus we evaluated whether the same mechanisms could be observed in the PAC1 receptor-expressing cell lines.…”
Section: Resultsmentioning
confidence: 90%
“…However, even at the higher concentration, dynasore did not significantly blunt the PACAP-induced ERK activation after 120 min (data not shown). Our earlier studies demonstrated that reducing treatment temperature from 37°C to ambient conditions (22-24°C) very effectively blunted the PACAP-induced PAC1 receptor internalization (31). Consequently, the temperature dependence of PACAP-induced ERK activation was examined to complement the endocytosis inhibitor studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,44 But there is yet no report on the signal transduction mechanism of trigeminal ganglion cell injury repair. This work showed that the genes of MAPK signal pathway molecules were significantly differentially expressed in MPAPO-treated injured mouse trigeminal ganglion cells.…”
Section: Discussionmentioning
confidence: 99%